Wheelchair as a nexus: understanding stigma in older adults with stroke in China - Chu, Qingqing; Zhang, Jing; Xi, Min; Liang, Miaosen; Wang, Xinyue; You, Donggui; Yu, Xinxin (Frontiers Media SA, 2026)
Purpose: After a stroke, older adults often face compounded stigma due to disability and aging, which can hinder their rehabilitation engagement and community participation. As wheelchairs are central to long-term stroke management, their design can either reinforce or mitigate such stigma. This study explores how wheelchair design attributes influence stigma among Chinese older adults with stroke and how these perceptions affect rehabilitation adherence and social reintegration. Method: A qualitative case study using semi-structured interviews was conducted with 15 older adults with stroke, 20 caregivers and rehabilitation stakeholders, and 24 members of the general public in Hubei, China. Data were thematically analyzed within an interdisciplinary rehabilitation context to identify how wheelchair-related meanings shape psychosocial and behavioral outcomes. Results: Five interrelated themes emerged: symbolic impact on personal identity, perceived visual aesthetics, adaptability across daily living contexts, autonomy and control in wheelchair use, and ease of operation in wheelchair maneuvering. Findings show that wheelchair design plays a dual role in the stigmatization process-it may serve as a visible marker of dependence or, if optimally designed, promote autonomy, dignity, and social acceptance. Conclusion: Wheelchair characteristics influence not only self-stigma and social perception but also rehabilitation adherence and quality of life among older adults with stroke. Addressing stigma through design requires integrating symbolic, sociocultural, and psychological dimensions into assistive device development. These findings highlight the need for interdisciplinary collaboration across design, rehabilitation, and integrated care networks to ensure equitable, stigma-free assistive solutions that enhance the well-being of older adults with stroke.